Analisis Komparatif Pemikiran Imam Syafi’i dan Relevansinya dengan Undang- undang No. 41 Tahun 2004 tentang Wakaf Muaqqat - Sholeh, Farhanuddin; Sofi, Muhammad Aminuddin (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2018)
The article discusses the relevance of Imam Syafi’i’s thought on waqaf Muaqqat with the act provisions No. 14 in 2004. The analysis based on some sources states that Imam Syafi’i applies law intinbath design, shahih hadiths in the texts, narrators and sanad after being takhrij. He argues that waqaf settlement is as a part of tabarru’ (releasing right). As a result, something that has been become a wakaf cannot be on sale, granted, legated due to the fact that does not belong to an individual but public. The act No. 41 in 2004, whereas, reveals that waqaf can belong for a life or a limited time. Therefore, waqaf can still become an individual’s right. Keywords : Waqaf Muaqqat, Imam Syafi’i’s thought, The Act No 41 in 2004.